Ammonium Sulphate (ZA) and Organic Fertilizer to Improve Yield and Quality of Shallot Bulb (Allium ascalonicum L.) on Recovered Ultisols - Nilla Kristina; Elara Resigia; Netti Herawati (Green Engineering Society, 2023)
In principle, shallot can adapt to all altitudes. But in West Sumatera, it is generally cultivated in the highland. The problem is the area in the highland is very limited while the area in lowland land is dominated by Ultisol soils. The type of soil in Agricultural Faculty experimental field at Andalas University is Ultisol (250 asl) but the chemical properties slightly change, such as nitrogen, phosphor and potassium higher than usual otherwise SO42- and Ca-dd is still very low. This study aimed to obtain the best organic fertilizer and ZA fertilizer on the growth, yield and quality of shallot bulb on recovered Ultisols. The research was a-two factorial experiment with 3 replications in Completely Randomized Design. The first factor is the application of various types of organic fertilizer, which include three levels which are guano, chicken manure, and oil palm empty bunches (OPEB). The second factor is ZA fertilizer dosage (0, 100, and 200 kg/ha). Data were analyzed using the F test with a 5% level, and if there were significant differences, the analysis continued with the Duncan’s New Multiple Range Test (DNMRT) at a 5% level. The result showed that the development of shallots on recovered Ultisols brings hope. The yield of chicken manure and guano are higher than oil palm empty bunches and in accordance with the description of Bima Brebes varieties around 9 t/ha. Even guano could produce dry bulbs around10,54 t/ha without giving ZA. Moreover, guano fertilizer gave the best Sulphur content on every dose of ZA.